RELATIONSHIP BETWEEN MINDFULNESS AND BULLYING BEHAVIOR AMONG SCHOOL CHILDREN: AN EXPLORATORY STUDY FROM PAKISTAN - Abid, Momina; Irfan, Muhammad; Naeem, Farooq (Journal of Postgraduate Medical Institute, 2017)
Objective: To find out the relationship between mindfulness and bullying behaviour among school children in Pakistan. Methodology: This cross sectional research was conducted in three private sector schools of Multan from March to August 2015. Two hundred gender- matched students, aged between 8 to 11 years were enrolled for the study. The assessments included Child and Adolescent Mindfulness Measure and Bullying-Behaviour Scale. Apart from the descriptive statistics, the relationship between mindfulness and bullying behaviours was analyzed using Pearson correlation. Gender differences was computed though independent t-test and ANOVA was performed to find out the effect of birth order on mindfulness and bullying behaviours. Results: The mean age of the sample was 9.49 ±1.26 years. There were 41 (20.5%) single children, 53 (26.5) first, 76 (38%) middle and 30 (15%) last children. Results showed that mindfulness and bullying behavior negatively correlated with each other (r =-.625). Significant differences in mindfulness and bullying behaviour among male and female children were found. Male students experienced more bullying as compared to female students and they also showed more mindfulness than female students (p<0.05). The difference for mindfulness and bullying behaviour scores of four groups of children with different birth orders (single, first, middle and last child) using ANOVA, showed significant effect of birth order (p <0.000 & 0.000 for mindfullness and bullying behaviour, respectively) Conclusion: There is a negative correlation between mindfulness and bullying behaviour and single children show high bullying behaviour.